Maksud Pendirian Koperasi Syariah 212 Mart di Deblod Sundoro di Kota Tebing Tinggi - Safiah Saffa Lubis; Mawaddah Irham (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2023)
The 212 Sharia Cooperative is a major national-scale business entity and was formed by Muslim leaders as a manifestation of the unified spirit of the 212 Action. This spirit is reflected in making the Sharia Cooperative 212 a forum for the spirit of economic growth to achieve people's economic independence, support the development of SMEs and make people financially responsible by realizing their products independently with the cooperative's business. The formation of the cooperative has a goal orientation for the welfare of members and the community in order to meet the needs of consumption, production and distribution as well as realizing social motivation to unite the community in economic activities for the creation of member welfare.